Synthesis and biological activity evaluation of hydrazone derivatives based on a Tröger's base skeleton - Kaplánek, Robert; Havlík, Martin; Dolenský, Bohumil; Rak, Jakub; Džubák, Petr; Konečný, Petr; Hajdúch, Marián; Králová, Jarmila; Král, Vladimír (Bioorganic & medicinal chemistry, 2015)
We report the design and synthesis of novel anticancer agents based on bis-hydrazones separated by a rigid Tröger's base skeleton. This novel approach combines a biologically active moiety (hydrazone) with this scaffold (Tröger's base) to construct DNA intercalators. Evaluation of the anticancer activity of these agents using seven cancer cell lines and two healthy cell lines found that several derivatives had potent anticancer activity and excellent selectivity indexes toward cancer cells. The antimicrobial activities were tested on a set of thirteen bacterial stains, but the prepared compounds were not active. Complexation studies using biologically important metal ions demonstrated that these compounds are able to bind Cu(2+), Fe(3+), Co(2+), Ni(2+) and Zn(2+). DNA intercalation studies showed that the compounds themselves do not interact with DNA, but their metallocomplexes do interact, most likely via intercalation into DNA.
Keywords: protinádorové látky; Drug Evaluation, Preclinical; buňky K562; apoptóza; Apoptosis; hydrazony; HCT116 buňky; Humans; preklinické hodnocení léčiv; HCT116 Cells; Antineoplastic Agents; Hydrazones; K562 Cells; lidé